Jesus and his promised Second Coming: Jewish eschatology and Christian origins - Ferda, Tucker S. (William B. Eerdmans Publishing Company, 2024)
"An examination and rebuttal of the critical consensus that Jesus of Nazareth did not predict or anticipate his post-death return"--